University students' perceptions of campus sustainability in Finland - Sotto, Rehna (2023)
Globalization contributes to the rapid economic growth, technological transformations, and development of human services. These excellent human innovations raise some questions about the risks to the environment, the individual, and society, bringing concerns about a sustainable future. The UN Sustainable Development Goals was born and its policy on sustainability flows from the international body to the member countries, to the local institutions, and finally to the constituents. With such, local institutions, like higher education institutions, formulate initiatives that are aligned with the 2030 Agenda on Sustainable Development. To gain support, a university, for instance, transfers sustainable development knowledge to its stakeholders. However, there are aspects of sustainability that are not yet fully understood, and sustainability is being defined in varied ways. This master’s thesis aims to provide insights into how university students view campus sustainability in Finland. This is done through conducting a two-week online survey of all attending university students at a Finnish university during the Spring semester of 2023. For the two-week duration, 100 university students voluntarily participated and answered the online questionnaire. The data gathered was analyzed using mixed methods in research. Inductive thematic analysis was performed to analyze the respondents’ answers to the open-ended questions. Whilst a chi-square test was used to ascertain whether there are differences in the categorical variables being tested and an independent sample t-test to present the significant connections between variables. The findings showed evidence that university students associated their understanding and definition of sustainability through an environmental lens and followed by the social dimension which can be related to other previous studies. From the thematic analysis, the respondents defined sustainability by speaking about their own actions in their daily life, their concerns towards others and the environment, and the consequences of their actions towards the future. Respondents also have similar views in terms of their concern towards the future/ present, their views on who should be held responsible for sustainability, and expressed that sustainability is important for them. However, a larger portion of both international and local students exhibit a commitment gap in terms of their participation in the university sustainability initiatives, and one-half of local students in their personal energy use attitudes. Also, a notable finding in the statistical analysis revealed that sustainability classes have no connection to participation in campus sustainability initiatives and energy use attitudes. Another important highlight of this thesis is that it uncovered the importance of communication and raising awareness about sustainability and sustainability initiatives on campus. This may help administrators in the improvement of sustainability communication channels and in the promotion of their sustainability actions at the university.